The Influence of Principal’s Leadership Style and Teacher’s Work Motivation on The Performance of State High School Teachers in Muara Kuang District - Zulyadi, Zulyadi; Lian, Bukman; Putra, Muhammad Juliansyah (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to describe how the principal’s leadership style and teacher’s work motivation influence the performance of public high school teachers in Muara Kuang District. The research was conducted at a public high school in Muara Kuang District. This research uses quantitative methods. The population of this research is State Senior High School teachers in Muara Kuang Sub-District, the sampling technique is used totaling sampling, namely the sample based on the total population of 41 respondents. Data collection is done by questionnaire, and documentation. Data were analyzed descriptively using the program SPSS 26 for windows. From the research results it can be concluded that. The results showed that there was a positive and significant influence of the principal’s leadership style, work motivation on the performance of public high school teachers in the Muara Kuang sub-district, which was shown from F-count of 4,894. These independent variables contributed 20.5% to the performance of public high school teachers in the Muara Kuang sub-district, while the remaining 79.5% was influenced by other variables not disclosed in this study.